Aerodynamic interactions of a Reusable Launch Vehicle model with different nose configurations. (December 2020) - Jia, Juhong; Fu, Debin; He, Zepeng
Abstract: The Two-Stage-To-Orbit (TSTO) hypersonic vehicle is an example of a Reusable Launch Vehicle (RLVs) configuration, and it has the advantages of small mass and large payload. A TSTO concept aircraft comprising a booster and a cruiser was proposed in this paper. The typical trapezoidal wing configuration was used as the booster and the wing spherical cone was used as the cruiser. Based on the three-dimensional hybrid LES/RANS numerical simulation method, the aerodynamic interference characteristics of different nose configurations in the cruise stage were studied, the pressure and heat flux distributions on the upper and lower surfaces of the cruise stage and the booster stage were calculated and analysed, the characteristics and mechanism of the aerodynamic interference between the two stages were revealed, and the structural changes of the flow field and the characteristics of the aerodynamic interference under different head configurations of the cruise stage were compared. The results show that the shock/shock interaction outside the blunt nose of the cruiser causes serious aerodynamic and thermal problems on the stagnation point. There are complex shock wave/boundary layer interactions and reflected shock trains between the two stages, which results in high-level pressure and heat flux on the surfaces. An alteration of the nose configuration can greatly improve the wall pressure and heat flux on the surface. The Bend cone model provides the greatest reduction in peak pressure and heat flux and is a suitable choice for an RLV cruiser. Highlights: Shock/shock interaction causes serious aerodynamic problems around blunt-nosed. There are complex shock wave/boundary layer interaction and reflected shock trains between two stages. The alteration of nose configuration can greatly improve the aerodynamic loads.